PENGARUH TINGKAT KONSENTRASI GULA PADA PROSES PENGOLAHAN MANISAN SALAK TERHADAP VITAMIN C DAN TINGKAT KESUKAAN KONSUMEN - Syane Palijama; Josephina Talahatu; Priscillia Picauly (AGRITEKNO: Jurnal Teknologi Pertanian, 2016)
Fruit of zallaca (Salacca edulis Reinw) can be made as food product. One of these products is zallaca sweet by using sugar as sweetener and preservative. The objective of the research was to study and determine sugar concentration level to maintain quality of zallaca sweet product. A complete randomized design was used in the research. A compeletely randomized design was used with eight treatments sugar concentration as follows 25, 30, 35, 40, 45, 50, 55, and 60% of sugar concentration. Result showed that using of 40% sugar could maintain the quality of zallaca sweet with concentration of vitamin C 0.033 mg, moisture content 76.56%, total acid 3.12%, total sugar 18,13% and pH 4.5.